Contrast-enhanced ultrasound: a viable diagnostic tool in predicting treatment failure after non-union revision surgery for upper- and lower-limb non-unions - Doll, Julian; Waizenegger, Stefan; Schmidmaier, Gerhard; Weber, Marc-André; Fischer, Christian (Ultrasound in medicine & biology, 2021)
Non-unions remain a major complication in the treatment of long-bone fractures and affect quality of life considerably. Both early detection and treatment of non-unions are essential to secure subsequent fracture union. Sufficient vascularization plays a key role in the healing process. The aim of this prospective study was to quantify the microperfusion within non-unions by means of contrast-enhanced ultrasound (CEUS) as early as 12 wk after non-union surgery and to examine the prognostic capability of CEUS in predicting treatment failure. Among 112 patients who had undergone non-union surgery, consolidation within 36 mo was achieved in 89 patients (“responders”), whereas 23 patients showed persistent non-unions (“non-responders”) and required further surgery. CEUS quantification parameters such as peak enhancement, wash-in area under the curve and wash-in perfusion index revealed significantly higher perfusion levels in “responders” compared with “non-responders” (p < 0.05). Receiver operator characteristic curve analysis revealed that persistent fracture non-unions could be predicted with a sensitivity/specificity of 88.7%/72.2% in lower-limb non-unions and a sensitivity/specificity of 66.7%/100.0% in upper-limb non-unions. CEUS is a suitable diagnostic tool in predicting treatment failure as early as 12 wk after non-union surgery and should be integrated into the clinical routine when deciding on revision surgery at an early stage.
Gesehen am 15.12.2021